Measuring Tax Efficiency: A Tax Optimality Index - Pascalis Raimondos-Møller; Alan D. Woodland (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
This paper introduces an index of tax optimality that measures the distance of some current tax structure from the optimal tax structure in the presence of public goods. In doing so, we derive a [0,1] number that reveals immediately how far the current tax configuration is from the optimal one and, thereby, the degree of efficiency of a tax system. We call this number the Tax Optimality Index. We show how the basic method can be altered in order to derive a revenue equivalent uniform tax, which measures the size of the public sector. A numerical example is used to illustrate the method developed.
Keywords: H21; H41; 330; tax optimality index; excess burden; distance function; Steuertheorie; Optimale Besteuerung; Excess Burden; Theorie